2008
DOI: 10.1042/bj20070867
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of three Arabidopsis thaliana mitochondrial dicarboxylate carrier isoforms: organ distribution, bacterial expression, reconstitution into liposomes and functional characterization

Abstract: Screening of the Arabidopsis thaliana genome revealed three potential homologues of mammalian and yeast mitochondrial DICs (dicarboxylate carriers) designated as DIC1, DIC2 and DIC3, each belonging to the mitochondrial carrier protein family. DIC1 and DIC2 are broadly expressed at comparable levels in all the tissues investigated. DIC1-DIC3 have been reported previously as uncoupling proteins, but direct transport assays with recombinant and reconstituted DIC proteins clearly demonstrate that their substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 48 publications
9
130
0
Order By: Relevance
“…Three genes, OXOPHYTODIENOATE RE-DUCTASE1 (OPR1), BON ASSOCIATION PROTEIN1 (BAP1), and the lysophosphatidic acid acyltransferase At4g24160, are related to lipid binding, metabolism, or homeostasis. The strongest expression after 1 h was observed for WRKY18 and WRKY40, which have partially redundant roles (Xu et al, 2006), and for PBP1, CALMODULIN LIKE39 (CML39), the transferase AT2g41640, and the dicarboxylate carrier DIC2, which could be involved in the transport of Pi across the inner mitochondrial membrane (Table II; Palmieri et al, 2008).…”
Section: Coexpression-based Gene Clustering Predicts Modules With Funmentioning
confidence: 99%
“…Three genes, OXOPHYTODIENOATE RE-DUCTASE1 (OPR1), BON ASSOCIATION PROTEIN1 (BAP1), and the lysophosphatidic acid acyltransferase At4g24160, are related to lipid binding, metabolism, or homeostasis. The strongest expression after 1 h was observed for WRKY18 and WRKY40, which have partially redundant roles (Xu et al, 2006), and for PBP1, CALMODULIN LIKE39 (CML39), the transferase AT2g41640, and the dicarboxylate carrier DIC2, which could be involved in the transport of Pi across the inner mitochondrial membrane (Table II; Palmieri et al, 2008).…”
Section: Coexpression-based Gene Clustering Predicts Modules With Funmentioning
confidence: 99%
“…In recent years several of these transporters have been cloned and investigated at the molecular and biochemical level (22,(31)(32)(33)(34). These studies revealed that some members of the MCF in plants can be present in the plastid membranes (35)(36)(37).…”
mentioning
confidence: 99%
“…Its high expression is accompanied by the expression of a dicarboxylate carrier, DIC (Table 1) [5 ,8]. Among the mitochondrial carriers that accept malate or OAA, DIC is unique as it catalyzes net carbon import as malate/phosphate or malate/sulfate exchange [41]. In case of phosphate exchange, the electrical field is capable of driving the exchange as malate is negatively charged twice and phosphate is negatively charged three times.…”
Section: Decarboxylation Modulementioning
confidence: 99%
“…If instead the C 4 acid is imported into the bundle sheath mitochondria as aspartate, the import protein remains unknown as the DICs of Arabidopsis do not accept amino acids [41].…”
Section: Decarboxylation Modulementioning
confidence: 99%
See 1 more Smart Citation